Testing robustness: A full-scale experimental test on a two-storey reinforced concrete frame with solid slabs. (1st August 2021) - Pérez Caldentey, Alejandro; Diego, Yolanda G.; Ariñez Fernández, Freddy; Santos, Anastasio P.
Highlights: Results of full-scale test of corner column removal carried out on a two storey building. Finite element modelling and comparison between observed and predicted damage patterns and deflections. Monitoring results including DIC, accelerometers and full characterisation of deflections using laser scan. Interpretation of results. Abstract: This paper presents the results of a full-scale robustness test carried out on a two storey building with two square reinforced concrete slabs (25 cm deep) with a span of 6.6 m, in which a corner column was suddenly removed. Despite the extreme action, and the fact that the slab was not designed for it, only relatively minor damage was observed, with a maximum deflection around 22 cm and apparently controled cracking patterns. The slab started working as a simply supported element along the symmetry axis of the structure supported on only 3 columns. The tests was modeled using Finite Element Analysis. It was observed that the model could capture very well the behaviour of the real structure, predicting very similar cracking patterns and deflections. The structure was shored two hours after the test because deflections were not yet fully stabilized. It is suspected that this increase of deflections could be related to the deterioration by torsional effects of the connection between the slab and columns on the first floor.